The use of spin desalting columns in DMSO‐quenched H/D‐exchange NMR experiments. (11th February 2013) - Chandak, Mahesh S.; Nakamura, Takashi; Takenaka, Toshio; Chaudhuri, Tapan K.; Yagi‐Utsumi, Maho; Chen, Jin; Kato, Koichi; Kuwajima, Kunihiro
Abstract Dimethylsulfoxide (DMSO)‐quenched hydrogen/deuterium (H/D)‐exchange is a powerful method to characterize the H/D‐exchange behaviors of proteins and protein assemblies, and it is potentially useful for investigating non‐protected fast‐exchanging amide protons in the unfolded state. However, the method has not been used for studies on fully unfolded proteins in a concentrated denaturant or protein solutions at high salt concentrations. In all of the current DMSO‐quenched H/D‐exchange studies of proteins so far reported, lyophilization was used to remove D2O from the protein solution, and the lyophilized protein was dissolved in the DMSO solution to quench the H/D exchange reactions and to measure the amide proton signals by two‐dimensional nuclear magnetic resonance (2D NMR) spectra. The denaturants or salts remaining after lyophilization thus prevent the measurement of good NMR spectra. In this article, we report that the use of spin desalting columns is a very effective alternative to lyophilization for the medium exchange from the D2O buffer to the DMSO solution. We show that the medium exchange by a spin desalting column takes only about 10 min in contrast to an overnight length of time required for lyophilization, and that the use of spin desalting columns has made it possible to monitor the H/D‐exchange behavior of a fully unfolded protein in a concentrated denaturant. We report the results of unfolded ubiquitin in 6.0M guanidinium chloride.